2010
DOI: 10.1016/j.biomaterials.2010.07.101
|View full text |Cite
|
Sign up to set email alerts
|

Cell–cell signaling in co-cultures of macrophages and fibroblasts

Abstract: The foreign body response (FBR) comprises a general, ubiquitous host tissue-based reaction to implanted materials. In vitro cell-based models are frequently employed to study FBR mechanisms involving cell signaling responses to materials. However, these models often study only one cell type, identify only limited signals, and cannot accurately represent the complexity of in vivo inflammatory signaling. To address this issue, a cell co-culture system involving two primary effector cells of the FBR, macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 67 publications
6
91
0
Order By: Relevance
“…This indicates that the IL-6 release was provoked by the effect of hydrophobicity of CH 3 SAM. The data also show that the IL-6 release from co-cultures on all surfaces after LPS treatment was much higher than the arithmetic sum of cytokine release on the corresponding macrophage and fibroblast mono-cultures, which indicates a cooperative action of both cell types in the co-cultures [11]. This is in line with previous reports, showing synergistic IL-6 and MCP-1 production in co-cultures of monocytes and vascular smooth muscle cells [65][66][67].…”
Section: Release Of Pro-inflammatory Cytokinessupporting
confidence: 88%
See 3 more Smart Citations
“…This indicates that the IL-6 release was provoked by the effect of hydrophobicity of CH 3 SAM. The data also show that the IL-6 release from co-cultures on all surfaces after LPS treatment was much higher than the arithmetic sum of cytokine release on the corresponding macrophage and fibroblast mono-cultures, which indicates a cooperative action of both cell types in the co-cultures [11]. This is in line with previous reports, showing synergistic IL-6 and MCP-1 production in co-cultures of monocytes and vascular smooth muscle cells [65][66][67].…”
Section: Release Of Pro-inflammatory Cytokinessupporting
confidence: 88%
“…These data suggest that fibroblasts did not produce significant quantities of TNF-a, but reduced TNF-a production of macrophages in the co-culture. Also, in other studies such reduction of TNF-a release by macrophages was found in the presence of fibroblast-released cytokines [11,68].…”
Section: Release Of Pro-inflammatory Cytokinesmentioning
confidence: 95%
See 2 more Smart Citations
“…This results mostly in a choice between assays investigating random or directional migration in 2D vs. 3D environments, 102,103 either of single cell types or of co-cultures. 104,105 In particular, different kinds of 3D migration assays have been established for studies of macrophages and other cell types, 102 including ex vivo explants (such as dermal explants), 106 tumor cell spheroids, 6 and matrices polymerized in vitro (e.g., Matrigel TM , fibrillar/gelled type I collagen, or native basement membrane). 17,55,58,59,107 However, each type of assay presents intrinsic disadvantages, for example, limited access for imaging processes in the case of thick 3D matrices.…”
Section: General Remarksmentioning
confidence: 99%